Parenting Geometrical Assemble Of Mini-Wooden Ship Learning Training Adobe Design To Develop Affection In Avoiding Violence Abuse For Children - Fina Rahmatika; Wirawan Pamuji (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
form after assembled one another. And it may assume to raise a student logical pattern in assembling for measuring rationality of thinking for elementary children in assembling the shapes into new complete forms of a ship simulation building with adobe design. The Research applies Development Design to create planning for elementary school levels in order that reforming shapes into a new form building and arranged by parents to plan it in order to create affection towards parents to impulse care domination for their children for avoiding abuse with practicing parents to make affection towards emotional acceleration. Geometrical Assemble is alike to measure Student abilities to test their logical platforms in assembling new complete forms in creating it after understanding the shapes of the geometrical forms at all conducted by the parents